(3OhQ GdCde GdoeRef aj GdJfHD HeXGgQ GdGcJFGH hGdjCS hbdb GdehJ dOi eQjVGJ eJdGReI GdCde GdYVdj Gddjaj (B/s Remainder of title - (3, eGLOI Hjhej ESeGYjd ehSis; (3TYHGf LGH Gddg QVhGf s; (3fhQG jSQj GdSjO CMeO s (2024)
(3JgOa GdOQGSI GdMGdjI Edi GdcTa Yf eOi ESgGe GdCde GdoeRef aj GdJfHD HeXGgQ GdGcJFGH hGdjCS hbdb GdehJ dOi eQjVGJ eJdGReI GdCde GdYVdj Gddjaj(B. (3HGdEVGaI Edi GdcTa Yf GdaQhb Hjfgf aj GdGcJFGH hGdjCS hbdb GdehJ aj VhA eJZjQj GdSf heOI GdeQV(B. (3hGYJeOJ GdOQGSI GdMGdjI Ydi GdefgL GdhUaj GdGQJHGWj GdaGQbj(B. (3hJchfJ GdYjfI ef (B(50) (3eQjVI oeTNUI HeJdGReI GdCde GdYVdj Gddjaj; JJQGhM CYeGQgf Hjf (B(21- 46) (3YGkeG, hoWHb Ydi CaQGO GdYjfI(B: (3ebjGS GdCde GdoeRef (B((3EYOGO GdHGMKI(B)(3, hebjGS (B"(3Hjc(B" (3ddGcJFGH (B((3JQLeI(B: (3CMeO eMeO YHOGdNGdb(B)(3, hebjGS(B"(3Hjc(B" (3ddjCS (B((3JQLeI hEYOGO GdHGMKI(B) (3hebjGS bdb GdehJ (B((3EYOGO GdHGMKI(B). (3hcTaJ fJGFL GdOQGSI Yf hLhO YdGbI GQJHGWjI ehLHI Hjf GdCde GdoeRef hcd ef GdGcJFGH hGdjCS, ceG cTaJ Yf hLhO YdGbI GQJHGWjI ehLHI Hjf GdCde GdoeRef ShGA ajeG jJYdb HGdOQLI GdcdjI, Ch GdechfGJ GdaQYjI heXGgQ bdb GdehJ ajeG jJYdb HGdOQLI GdcdjI hGdechfGJ GdaQYjI dOi eQjVGJ eJdGReI GdCde GdYVdj Gddjaj, hdcf dG JhLO YdGbI Hjf GdeXGgQ GdLSejI ddCde GdoeRef hGdeXGgQ GdLSejI hGdaSjhdhLjI, hGdGfaYGdjI, hGdeYQajI hGdOQLI GdcdjI dbdb GdehJ; ceG CXgQJ GdfJGFL ESgGe GdCde GdoeRef ESgGkeG OGkdG aj GdJfHD HeXGgQ GdGcJFGH hGdjCS hbdb GdehJ(B. (3HjfeG HjfJ GdfJGFL CjkVG Yf YOe hLhO aQhb aj GdGcJFGH hGdjCS aj VhA eJZjQj GdSf heOI GdeQV hbdb GdehJ aj VhA eJZjQ GdSf, hJhLO aQhb aj HYV eXGgQ bdb GdehJ hGdOQLI GdcdjI aj VhA eJZjQ eOI GdeQV aj GJLGg GdYeQ GdCUZQ(B.s
The current study aims to reveal the role of chronic pain in predicting the manifestations of depression, despair and death anxiety among female patients with fibromyalgia syndrome, and to determine the differences between them in the manifestations of depression, despair and death anxiety based on age and duration of illness.The current study based on the descriptive correlational differential approach. The sample consisted of (50) female patients diagnosed with fibromyalgia syndrome. Their ages ranged between (21-46) years. The sample members were applied to: the chronic pain scale (prepared by the researcher), the Beck depression scale (translated by Ahmed Muhammad Abdel Khaleq), the Beck despair scale (translated and prepared by the researcher), and the death anxiety scale (prepared by the researcher). The results of the study revealed the existence of a positive correlation between chronic pain and both depression and despair. It also revealed the existence of a positive correlation between chronic pain, whether with regard to the total score or subcomponents, and the manifestations of death anxiety with respect to the total score and subcomponents among female patients with fibromyalgia syndrome. However, there is no relationship between the physical manifestations of chronic pain and the physical, physiological, emotional, and cognitive manifestations and the total score for death anxiety, The results also showed that chronic pain makes a significant contribution to predicting the manifestations of depression, despair, and death anxiety. While the results also showed that there were no differences in depression and despair in light of the variables of age and duration of illness, and death anxiety in light of the variable of age, and there were differences in some aspects of death anxiety and the total score in light of the variable of duration of illness in the direction of younger age.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B126-142.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3Yde GdfaS GdYdGLis; (3GdCde GdoeRefs -- (3GdGcJFGHs -- (3GdjCSs -- (3bdb GdehJs -- (3eJdGReI GdCde GdYVdj Gddjajs